Establishment and Application of a Multiple Cross Displacement Amplification Coupled With Nanoparticle-Based Lateral Flow Biosensor Assay for Detection of Mycoplasma pneumoniae - Wang, Yacui; Wang, Yi; Quan, Shuting; Jiao, Weiwei; Li, Jieqiong; Sun, Lin; Wang, Yonghong; Qi, Xue; Wang, Xingyun; Shen, Adong (Frontiers in Cellular and Infection Microbiology, 2019)
Mycoplasma pneumoniae (M. pneumoniae) is responsible for pneumonia, and is causative agent of other respiratory tract infections (e.g. bronchiolitis and tracheobronchitis). Herein, we established and applied a multiple cross displacement amplification (MCDA) coupled with nanoparticle-based lateral flow biosensor (LFB) assay (MCDA-LFB) for rapid, simple and reliable detection of target pathogen. A set of ten primers was designed based on M. pneumoniae-specific P1 gene, and optimal reaction conditions were found to be 30 min at 65ºC. The detection results were visually reported using biosensor within 2 min. The M. pneumoniae-MCDA-LFB method specifically detected only M. pneumoniae templates, and no cross-reactivity was generated from non-M. pneumoniae isolates. The analytical sensitivity for this assay was 50 fg of genomic templates in the pure cultures, as obtained from colorimetric indicator and real-time turbidimeter analysis. The assay was applied to 197 oropharyngeal swab samples collected from children highly suspected of M. pneumoniae infection, and compared to culture-based method and real-time PCR assay. The detection rates of M. pneumoniae by culture-based method, real-time PCR assay and MCDA-LFB assay were 8.1%, 33.0%, 52.3%, respectively, which indicated the MCDA-LFB assay was superior to culture-based method and real-time PCR method for detection of target agent. Using this protocol, 25 min for rapid template extraction followed by MCDA reaction (30 min) combined with LFB detection (2 min) resulted in a total assay time approximately 60 min. In conclusion, MCDA-LFB assay established in this report was simple, rapid, sensitive and reliable assay to detect M. pneumoniae strains, and can be used as a potential diagnostic tool for M. pneumoniae in basic and clinical laboratories.